Of figures and types: brokering knowledge and migration in Indonesia and beyond. (May 2015) - Lindquist, Johan; BANDAK, ANDREAS; HØJER, LARS
<x xml:space="preserve">Abstract</x> This paper takes the broker as an entry‐point for considering the problem of exemplification in anthropology. In particular, it approaches this problem by way of the relationship between figure and type, or between example and theoretical exemplar. While the figure is contingent on a specific socio‐historical context, the type consciously accentuates particular characteristics in order to form the basis for comparison. More specifically, the paper approaches this relationship by considering the broker as type in relation to two specific figures in the current regime of transnational Indonesian migration, namely the NGO outreach worker and the informal labour recruiter, both identified as 'field agents', or petugas lapangan, in Indonesia. By way of juxtaposition the paper discusses the oscillation between figure and type in order to consider biases in the anthropological literature on brokers – most notably that the the broker is inherently amoral if not immoral – while suggesting that the broker is an exemplary methodological starting‐point for contemporary anthropology.